THE BALANCE OF IMPLEMENTATION BETWEEN PROJUSTITIA AND IMMIGRATION ADMINISTRATION ACTION - Budy Mulyawan; Silvester Yansen Halawa; Raden Kevin Fabio Winata (Polteknik Imigrasi, 2018)
In the current era of globalization, it is very common for humans to travel between countries. The freedom of human movement to move between countries is a basic or human rights guaranteed in the constitution. This migration right is regulated in Article 28E of the 1945 Constitution (Amendment), which determines that: